2016
DOI: 10.1002/2016ja023384
|View full text |Cite
|
Sign up to set email alerts
|

Highly localized unique electrodynamics and plasma irregularities linked with the 17 March 2015 severe magnetic storm observed using multitechnique common‐volume observations from Gadanki, India

Abstract: In this paper we study equatorial electrodynamics and plasma irregularities linked with the 17 March 2015 severe magnetic storm in the Indian sector by using common volume observations made by the Gadanki Ionospheric Radar Interferometer, airglow imager, Digisonde, and GPS receiver established at Gadanki (13.5°N, 79.2°E). Observations show that with the initiation of the storm at ~06:00 UT on 17 March, which happened to be midday in the Indian sector, the low‐latitude ionosphere responded in tune with the stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 23 publications
3
52
0
Order By: Relevance
“…Ma and Maruyama () reported that a storm‐induced super plasma bubble exhibited a much slower eastward drift velocity in contrast to the quiet time, and they attributed the slow eastward drift to the storm time westward zonal wind. Reversal of zonal drift of the storm time irregularities form large eastward to westward due to the disturbance dynamo effect was also studied by Patra et al (). The westward turning of zonal drift velocities of the FAIs in our observation probably resulted from the storm‐related thermospheric disturbance winds that have a strong westward component in low‐latitude regions.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Ma and Maruyama () reported that a storm‐induced super plasma bubble exhibited a much slower eastward drift velocity in contrast to the quiet time, and they attributed the slow eastward drift to the storm time westward zonal wind. Reversal of zonal drift of the storm time irregularities form large eastward to westward due to the disturbance dynamo effect was also studied by Patra et al (). The westward turning of zonal drift velocities of the FAIs in our observation probably resulted from the storm‐related thermospheric disturbance winds that have a strong westward component in low‐latitude regions.…”
Section: Discussionmentioning
confidence: 87%
“…Numerous studies (e.g., Yokoyama et al, ; Patra et al, ) have shown that the zonal drift of the nighttime plasma irregularities is eastward under quiet conditions. During magnetically disturbed conditions, the zonal velocities of plasma irregularities may slow down and/or even reverse to westward (Abdu et al, ; Basu et al, ; Ma & Maruyama, ; Patra et al, ). In general, the zonal motion of the irregularities follows that of the ambient plasma.…”
Section: Discussionmentioning
confidence: 99%
“…The PPEFs due to sudden southward (northward) turnings of IMF Bz are eastward/westward (westward/eastward) on the daytime/nighttime sector and have lifetimes of tens of minutes to several hours (Huang, ; Tsurutani et al, , and the references therein). Regional‐scale ionospheric responses to the continuous PPEFs under steady and long‐duration southward IMF Bz have been widely investigated (e.g.Fagundes et al, , Li et al, , Mannucci et al, , Patra et al, ). By using GPS receiver data obtained during the “Halloween” storm of 29–30 October 2003, Mannucci et al () reported that the eastward PPEF results a significant strengthening and poleward expansion of the equatorial ionization anomaly (EIA), producing a “super‐fountain” effect with total electron content (TEC) enhancements up to 250% at low to middle latitudes in the Pacific sector.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of studies on the longitudinal and latitudinal variations of EPBs during geomagnetic storms have been performed. It was revealed that the EPB development can be totally suppressed, be confined to a limited longitude/latitude range, be significantly enhanced to extend to middle latitudes, or be triggered successively in a large longitude region (e.g., Abdu et al, 2003;Carter et al, 2016;Li et al, 2009Li et al, , 2010Patra et al, 2016;Tulasi Ram et al, 2008). In East Asia, observations have shown that storm time midlatitude plasma bubble is not a rare phenomenon (e.g., Li et al, 2009;Ma & Maruyama, 2006;Sahai et al, 2009), whereas in the European sector, the first detection of midlatitude plasma bubble was reported more recently (Cherniak & Zakharenkova, 2016;Katamzi-Joseph et al, 2017).…”
Section: Introductionmentioning
confidence: 99%